The Effect Of Work Environment, Reward And Punishment On Employee Performance At Pt. Haleyora Powerindo Batam - H, Harry Aulia; Hidayat, Rizki (Universitas Batam, 2021)
The purpose of this study was to analyze the effect of work environment, reward and punishment on employee performance at PT. Haleyora Powerindo Batam. The dependent variable in this study is employee performance (Y). Meanwhile, the independent variables are work environment (X1), reward (X2) and punishment (X3). The population used in this study were employees of PT. Haleyora Powerindo Batam with a total of 172 employees, while the samplng technique was purposive sampling and obtained a sample of 120 respondents. The research method used is descriptive and quantitative methods for the data analysis method, the multiple linear regression analysis method uses the SPSS 25.0 program. The results showed that variables had a significant positive effect on employee pertormance at PT. Haleyora Powerindo Batam. The value of R Square on the reward and punishment variables affecting performance is 42.2%.